Cultural Industries for Sustainable Development? - Stylianou-Lambert, Theopisti; Dessein, Joost; Mihailova, Marina; Soini, Katriina; Spinozzi, Paola; Fairclough, Graham; Cicerchia, Annalisa; Horlings, Lummina; Johannisson, Jenny; Kangas, Anita; Lapka, Miloslav; Sesic -Dragicevic, Milena; et al. (Jyväskylä University Press, 2015)
Policy documents that highlight the importance of cultural industries are becoming increasingly common throughout the world, even though culture is almost invisible in the Millennium Development Goals. This is also the case in countries that are in the ‘low human development’ category, such as Burkina Faso, positioned by the UNDP at 183 out of 187 countries. Its population of approaching 20M contains more than 60 ethnic groups, and studying policy here offers a compelling view of the creative economy debate in a culturally diverse context, and highlights local-global policy interaction
Keywords: Cultural Industries; Sustainable Development